Influence of hemp roving twist and fiber apparent parameters on the mechanical properties and water absorption of quasi-unidirectional composites. Issue 21 (November 2022) - Lu, Chao; Wang, Chunhong; Salleh, Kushairi Mohd; Zakaria, Sarani; Chen, Yasong; Tong, Jianfeng; Deng, Nanping; Zuo, Qi; Yan, Yuhuan
The finite length of natural fibers makes them frail and unable to perform and be engineered as excellent composite reinforcements. Hence, roving formations and weaving techniques have been employed to overcome these weaknesses and have been used as an alternative reinforcement in continuous quasi-unidirectional hemp composites (QUDHCs). Tensile, flexural, and water absorption tests were conducted on nine QUDHCs. It was concluded that adopting the warp consolidation weaving technique significantly improved the mechanical stability of the QUDHCs and negatively affected the water absorption properties. Nevertheless, adverse effects of a roving twist on the mechanical properties of QUDHCs were found when a 40 turn/m roving was used as the weft. Meanwhile, the mechanical properties of QUDHCs were strongly dependent on the fiber quality produced after roving twists. The roving twists numbers affected the water absorption of QUDHCs in different ways when there is/no warp yarn interweaving with the roving in the preform. In contrast, the moisture rate gain increased with the increment of roving twists in the case of the warp yarn and weft roving interweaving in the preform. The results in this study highlight the feasibility of improving the mechanical and water absorption properties by hemp roving fiber formations and weaving techniques, which is beneficial for the textile-structure composite industry.